2015
DOI: 10.1186/s12913-014-0668-0
|View full text |Cite
|
Sign up to set email alerts
|

Health worker perspectives on barriers to delivery of routine tuberculosis diagnostic evaluation services in Uganda: a qualitative study to guide clinic-based interventions

Abstract: BackgroundStudies of the quality of tuberculosis (TB) diagnostic evaluation of patients in high burden countries have generally shown poor adherence to international or national guidelines. Health worker perspectives on barriers to improving TB diagnostic evaluation are critical for developing clinic-level interventions to improve guideline implementation.MethodsWe conducted structured, in-depth interviews with staff at six district-level health centers in Uganda to elicit their perceptions regarding barriers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
68
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 25 publications
15
68
0
2
Order By: Relevance
“…Health workers perceived that there were multiple factors responsible for lost to follow up among patients that started ART immediately, topmost among them was financial difficulties, making it challenging to afford transport to clinic and payment for investigations. This finding was consistent with those previously reported [26-28]. Maskew et al , in their study in South Africa, conducted among 182 HIV positive patients who missed follow up appointments, and contacted through telephone calls, reported that a majority of their patients cited financial difficulties and inability to pay for transportation costs as major reasons for missed appointments [26].…”
Section: Discussionsupporting
confidence: 91%
“…Health workers perceived that there were multiple factors responsible for lost to follow up among patients that started ART immediately, topmost among them was financial difficulties, making it challenging to afford transport to clinic and payment for investigations. This finding was consistent with those previously reported [26-28]. Maskew et al , in their study in South Africa, conducted among 182 HIV positive patients who missed follow up appointments, and contacted through telephone calls, reported that a majority of their patients cited financial difficulties and inability to pay for transportation costs as major reasons for missed appointments [26].…”
Section: Discussionsupporting
confidence: 91%
“…Although Uganda made remarkable progress during the MDG era, a number of barriers were identified, including inept case management, insufficient resources, and frail health systems, particularly related to programs targeting malaria and tuberculosis (Yeka et al ., ). Similarly, challenges were reported in programs aimed at reducing infant and maternal mortality (Cattamanchi et al ., ). Omona () examined the impact of good governance in CQI to achieve the MDGs, and implied that the role of governance can be viewed in terms of leadership and policy formulations to ensure high quality care for patients.…”
Section: Discussionmentioning
confidence: 97%
“…However, lack of clinical suspicion for TB and treatment with antibiotics has been associated with diagnostic delays in several other studies [10, 16, 17]. Previous qualitative work in Uganda suggests that in addition to lack of clinical suspicion for TB, barriers to diagnostic testing include lack of knowledge/training as well as lack of motivation due to limited health care worker time and discomfort working with TB patients and handling sputum specimens [18]. Further qualitative work is needed within our local context to understand provider behavior and reasons for lack of sputum ordering.…”
Section: Discussionmentioning
confidence: 99%